2004
DOI: 10.1253/circj.68.1146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Sauna Treatment on Ventricular Arrhythmias in Patients With Chronic Heart Failure

Abstract: BackgroundThe aim of the present study was to determine whether repeated 60°C sauna treatment improves cardiac arrhythmias in chronic heart failure (CHF) patients, because ventricular arrhythmias are an important therapeutic target in CHF. Methods and Results Thirty patients (59±3 years) with New York Heart Association functional class II or III CHF and at least 200 premature ventricular contractions (PVCs)/24 h assessed by 24-h Holter recordings were studied. They were randomized into sauna-treated (n=20) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 43 publications
5
134
0
2
Order By: Relevance
“…Notably, majority of Finnish people use sauna regularly and access to sauna is not limited by socioeconomic background or other reasons. 1,17 The view of sauna as an indicator of SES is indeed stronger and more common in non-Finnish cultures than in Finland. Although we accounted for SES, it is not possible to exclude completely that sauna is not an indicator of economic, familial, or working traits.…”
Section: Limitationsmentioning
confidence: 99%
“…Notably, majority of Finnish people use sauna regularly and access to sauna is not limited by socioeconomic background or other reasons. 1,17 The view of sauna as an indicator of SES is indeed stronger and more common in non-Finnish cultures than in Finland. Although we accounted for SES, it is not possible to exclude completely that sauna is not an indicator of economic, familial, or working traits.…”
Section: Limitationsmentioning
confidence: 99%
“…12 The dry sauna method sauna has been studied extensively by several groups of Japanese researchers at the University of Kagoshima. 2,[11][12][13][14][15][16][17] Those researchers have utilized this approach in subjecting patients with heart failure to dry sauna at a temperature of 60°C for a period of 15 minutes per session.…”
Section: Sauna Bathing/dry Sauna Methodmentioning
confidence: 99%
“…An additional study with 30 NYHA class II and III patients reported a 73% reduction in premature ventricular contractions (from 3161 to 848 per 24-hour period) following 2 weeks of thermal therapy. 13 Other forms of arrhythmias, such as couplets and episodes of ventricular tachycardia, were found to be decreased by 50% and 75%, respectively.…”
Section: Cardiac Arrhythmias and Suddenmentioning
confidence: 95%
See 1 more Smart Citation
“…The therapy was also found to increase circulation, lower blood pressure, lower blood sugar, and help in weight loss. Another study looked at the effects of repeated 60°C sauna treatments on the cardiac arrhythmias in chronic HF patients and found that the treatments were successful [65]. Crinnion [66] showed a growing body of evidence on the clinical use of saunas for therapeutic purposes.…”
Section: Infrared Saunasmentioning
confidence: 99%